Immigrants' Wage Growth and Selective Out-Migration - Govert Bijwaard; Jackline Wahba (Institute for the Study of Labor (IZA), 2014)
This paper examines immigrant wage growth taking into account selective out-migration using administrative data from the Netherlands. We also take into account the potential endogeneity of the immigrants' labor supply and their out-migration decisions on their earning profiles using a correlated competing risk model, but we also use standard estimations as done in previous literature. We distinguish between two types of migrants: labor and family migrants given their different labor market and out-migration behavior. We find that simple models lead to biased estimates of the wage growth of immigrants. Controlling for the selective out-migration and endogeneity of labor supply, we find that labor out-migrants are positively selected but family out-migrants are negatively selected. Furthermore, the findings underscore the importance of taking into account the endogeneity of labor supply and out-migration when estimating immigrants' wage growth.
Keywords: F22; J61; C41; 330; migration dynamics; labor market transitions; competing risks; immigrant assimilation; income growth